Fodor's London 2026 - Jemil, Nori; O'Neill, James (Travel writer); Orton, Toby; Stein, Ellin; Wijeratna, Alex (Fodor's Travel, a division of MH Sub I, LLC, dba Internet Brands, 2025)
"Whether you want to pose in front of Big Ben's Elizabeth Tower, explore the Tower of London, or visit the royal family at Buckingham Palace, the local Fodor's travel experts in London are here to help! Fodor's London guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This new edition has an easy-to-read layout, fresh information, and beautiful color photos"--